Pengaruh High Intensity Interval Training terhadap Kebugaran Jasmani Korps Sukarela Palang Merah Indonesia Kota Bogor - Achwan, Achwan; Nurjanah, Anisa Rahmawati; Agustina, Dwi (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2024)
Background: Fitness is the ability to meet life’s demands effectively without fatigue. The results of the researcher's survey of the Indonesian Red Cross (PMI) Bogor City Voluntary Corps (KSR) members showed low average physical activity (370 METs). High-Intensity Interval Training (HIIT), involving alternating high-intensity exercise with moderate recovery periods or rest, can improve fitness. Aim: This research aimed to determine HIIT's effect on physical fitness. Method: The quasi-experimental study included 36 KSR PMI Bogor City members meeting specific criteria. Fitness was measured using the modified Harvard step test and agility t-test. HIIT was conducted 3 times a week for 4 weeks. Data was processed using SPSS software. Result: The Shapiro-Wilk test confirmed normal data distribution, and the Levene test confirmed homogeneity. The paired sample t-test showed a significant improvement in the treatment group’s cardiorespiratory endurance (p=0.00) but not in the control group (p=0.150). For agility, the treatment group also showed significant improvement (p=0.00), whereas the control group did not (p=0.078). The independent t-test revealed significant differences in cardiorespiratory endurance (p=0.000) and agility (p=0.043) between the groups. Conclusion: HIIT significantly improves physical fitness, cardiorespiratory endurance, and agility among KSR PMI Bogor City members. Recommendation: Future research should control other factors influencing physical fitness.